Improving the Knowledge of Health Cadres for Stunting Prevention through Emotional Demonstration Technique - Etrawati, Fenny; Lionita, Widya; Amalia, Ella; Rahmawati, Fuji; Meilinda, Nurly; Rahmawaty, Annisa (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2023)
Stunting has become a dietary concern in Indonesia. Ogan Komering Ilir district of South Sumatra Province has a stunting prevalence exceeding 20%, highlighting a significant public health concern according to WHO. Addressing this challenge requires the active involvement of health cadres, who play a pivotal role in enhancing maternal and child health. This study aimed to enhance the knowledge of health cadres in stunting prevention through the application of the emotional demonstration method at the village level. A total of 23 active cadres from the healthcare system were purposefully selected to participate in this activity. The experiment group, consisting of 12 cadres, underwent training using the emotional demonstration method through interactive games, while the control group, totaling 11 cadres, followed conventional methods, such as lectures. The activity was held with separate sessions for each group. The participants’ knowledge was measured using questionnaires covering the understanding of stunting, exclusive breastfeeding, complementary foods, anemia, and sources of nutrients. Data were analyzed using a dependent t-test. Average pre-post knowledge gains were 1.15 scores higher for experiment groups compared to 0.19 scores higher for control groups. Statistically significant changes in knowledge scores were observed in the experiment group (p = 0.002), while the control group showed insignificant changes (p = 0.321). Education activities employing emotional demonstration through interactive games are effective in increasing knowledge of stunting prevention.